Olfactory Neuroblastoma: A 15-Year Single Institution Experience - Hosseini, Sare; Khademi, Bijan; Safari, Sima; Mohammadianpanah, Mohammad (Reports of Radiotherapy and Oncology, 2015)
Background: Olfactory neuroblastoma or esthesioneuroblastoma is a rare malignant neoplasm of the olfactory neuroepithelium. Objectives: This study aimed to investigate the clinical presentation, characteristics and treatment outcome of fourteen patients with olfactory neuroblastoma. Patients and Methods: This retrospective study reviewed and analyzed 14 patients with olfactory neuroblastoma during the last 15 years at two referral tertiary academic hospitals of Shiraz University of Medical Sciences. Patients under 16 years old were excluded from the study. Kadish classification was used for staging the tumors. In addition, the tumors were histopathologically graded according to Hyams’ grading classification. Results: There were 6 women (43%) and 8 men (57%) ranging from 16 to 56 years old, with a median age of 40 years at diagnosis. Nasal obstruction (93%), facial or sinus pain (57%), and nasal bleeding (43%) were the most frequent presentation. Two patients (14%) had stage A, 3 (21.5%) had stage B, 6 (43%) had stage C, and 3 (21.5%) had stage D disease. After initial treatment, five patients developed local and/or distant recurrent disease. After a median follow-up of 73 (range 14 - 108) months for surviving patients, 10 patients (71.5%) were alive and without disease, one (7%) was alive with disease, and 3 (21.5%) died due to the disease. The 5-year disease-free and overall survival rates were 71.4% and 75.7%, respectively. Conclusions: At our center, patients with olfactory neuroblastoma tend to present at advanced stages; therefore, combined local treatment and incorporation of chemotherapy may improve outcome.